(untitled) (Conference on English Language Teaching, 2025)
This research analyzes social opinions made through the medium of online comments on Israel’s military attacks on Gaza’s hospitals, observed on Al Jazeera news website’s comment pages. Based on a qualitative descriptive analysis and Appraisal Theory, specifically the Judgment dimension this study seeks to demystify internet users’ judgment and opinion on the matter. The analysis yielded 84 instances of judgment that fell into the Social Esteem and Social Sanction categories. Under Social Esteem, 13 comments were identified and grouped under Capacity (12) and Tenacity (1). Conversely, Social Sanction was more evident with 71 comments comprising Veracity (17) and Propriety (54). The latter category was utilized largely to evaluate both Israel’s and Hamas’s actions against established social norms and sanctions. The results suggest that public communication is not merely evaluative but also shaped by underlying theological ideologies and personal beliefs. Most internet users situate their comments within religious or ideological frameworks, thereby deciding their evaluation of the conflict. The paper underlines the intricate relationship among language, ideology, and public opinion in online discussion, revealing how virtual communities frame and express opinions about contentious geopolitical conflicts.